1984
DOI: 10.1002/atr.5670180107
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transit‐system characteristics

Abstract: The transit industry is facing declining ridership and increasing costs with no apparent end in sight. This paper takes the view that totally new solutions are needed. The approach is to examine the equation for total cost of a transit system per passenger-mile to determine how to configure a new system to minimize this quantity. Term-by-term analysis leads to derivation of a consistent set of optimum characteristics. Guideway costs are minimized by distributing the load in very small capsules. The fleet cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…Cost ®gures for DRT are based on interviews with managers at the Santa Clara Valley Transportation Agency and Sacramento Paratransit, and on the Lea and Elliott Transit Compendium (1975). Cost ®g-ures for PRT are based on information from system developers whose systems can be considered to be in an advanced state of development, including Raytheon 2000 (Schupp, 1996), Taxi 2000 (Anderson, 1985(Anderson, , 1988a, and Yeoida systems (Woobo Architects and Engineers Inc, 1994). It is assumed that projects will be built in the year 2010 and funded with a 25-yr bond.…”
Section: Consumer Welfare Resultsmentioning
confidence: 99%
“…Cost ®gures for DRT are based on interviews with managers at the Santa Clara Valley Transportation Agency and Sacramento Paratransit, and on the Lea and Elliott Transit Compendium (1975). Cost ®g-ures for PRT are based on information from system developers whose systems can be considered to be in an advanced state of development, including Raytheon 2000 (Schupp, 1996), Taxi 2000 (Anderson, 1985(Anderson, , 1988a, and Yeoida systems (Woobo Architects and Engineers Inc, 1994). It is assumed that projects will be built in the year 2010 and funded with a 25-yr bond.…”
Section: Consumer Welfare Resultsmentioning
confidence: 99%
“…In the type of transit system envisioned here, however, a larger group can easily take two vehicles, which would be only a few seconds apart. Anderson (1984) showed that the O&M cost per place-mile (O&M cost per vehicle-mile divided by vehicle capacity) of transit systems is remark-ably independent of vehicle size. The use of small vehicles therefore does not increase the O&M cost of a vehicle fleet of a given capacity.…”
Section: Vehicle Fleet Capital Costmentioning
confidence: 99%
“…In off-peak periods, vehicle frequency must decrease, causing further decline in the load factor. With scheduled service, daily load factors average up to about 0.20 (Anderson, 1984).…”
Section: Vehicle Fleet Operating and Maintenance Costsmentioning
confidence: 99%
“…There is a substantial amount of peerreviewed literature on the general design and optimization of transit service in a given corridor [5][6][7][8][9][10][11]. The relationship between rail line location within a corridor and land use was explored in [3] and, [12].…”
Section: Introductionmentioning
confidence: 99%